Demand for international reserves: a case for reserves accumulation in Nigeria (2011)
This paper examined the determinants of international reserves holding in Nigeria, where a huge amount of foreign reserves is necessary to ensure good macroeconomic policy and international credit worthiness. Adopting a dynamic modeling approach combined with the Mizon-Richard encompassing test, both precautionary and mercantilist motives explain holding of foreign reserves in Nigeria. Specifically, the current account variability and past levels of external reserves drive reserve holding in the short run. In the long run, the former and the money supply are significant determinants. Therefore, enhancement of exports through support for quality and competitiveness of non-oil exports are key to reserves management.